Effective photoelectrocatalysis of levofloxacin antibiotic with Ti/IrO2[sbnd]Nb2O5 in environmental samples - Fernandes, Carlos H.M.; Goulart, Lorena A.; Gonçalves, Roger; Santos, Géssica O.S.; Zanoni, Maria V.B. [UNESP]; Mascaro, Lucia H.; Lanza, Marcos R.V. (Elsevier, 2024)
This work reports the development and application of a highly efficient catalyst based on IrO2 and Nb2O5 for the degradation of the antibiotic Levofloxacin (LFX) in simulated and real surface water samples. The IrO2[sbnd]Nb2O5 films, which were obtained by modified Pechini method, were deposited on a titanium substrate, leading to the production of Ti/IrO2[sbnd]Nb2O5 electrode. After being subjected to morphological, structural and electrochemical characterization, the Ti/IrO2[sbnd]Nb2O5 electrode was applied for the degradation of LFX using different processes, including electrolysis (EC) and photoelectrolysis (PhEC), and the results obtained were compared to that of UV–Vis irradiation-based photolysis. The application of the PhEC process led to a relatively higher and faster removal of LFX in the water matrices investigated, where 100% degradation rate and about 70% mineralization rate were obtained at the end of 1.5 h of treatment, compared to the individual photolysis and EC processes. The results obtained from quenching tests showed that LFX degradation under the PhEC process may be associated with the presence of active radicals, such as HO•, SO4•− and O2•−, in addition to the e−/h+ pair formed with the incidence of light during treatment. Apart from excellent photoelectrocatalytic activity and high stability, the Ti/IrO2[sbnd]Nb2O5 electrode exhibited high electrochemically active surface area (ECSA). The excellent results obtained from the application of the PhEC process in terms of TOC removal and the remarkable catalytic properties of Ti/IrO2[sbnd]Nb2O5 point to the high efficiency of the system proposed in this study when applied for the treatment and removal of organic pollutants from real water samples.
Keywords: Advanced oxidation process; Antibiotics; Iridium-Niobium-based electrode; Pechini method; Photoelectrocatalysis; Real water